Pengembangan Media Pembelajaran Bahasa Arab berwawasan Sains berbasis Mobile Android - Wakhidati Nurrohmah Putri; Arif Billah (LISANIA: Journal of Arabic Education and Literature, 2019)
This study aimed at developing a science-based Arabic language learning media based on Android mobile. The research method used was Research and Development. Validators included material and media experts, and practitioners. The testing phase included: limited phase I, II, and field trials. The subjects of the trial were students of the Department of Tadris IPA IAIN Salatiga. The data were obtained from documentation, questionnaire, and interviews. The results of the study were in the form of android-based software called “Bahasa Arab 1” with the validity score of 4.26 (very good); and practicality of 4.25 (very good). The results of the assessment through the limited phase I, II, and field trial stages are 4.30 (very good); 4,41 (very good); and 4.44 (very good). The characteristics and advantages of the product are:  ability to be downloaded through google play store; ability to run offline; available learning objectives, training materials and evaluation of competency tests interactively.